The Determinants of Environmental Performance: A Study on Indonesia Listed Firms - Amalia Tresna Fadhilah; Harry Suharman; Sofik Handoyo (Universitas Padjadjaran, 2021)
This study aims to analyse and examine the determinants of environmental performance in companies. The results of this study are expected to increase the company's concern for environmental sustainability. The population in this study were all companies listed on the Indonesia Stock Exchange in the 2017-2020 period. The samples in this study were 11 companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This research was conducted with a quantitative approach. The results show that financial performance, corporate governance, and market capitalisation positively and significantly affect environmental performance.